Optimasi Pemilihan Supplier Kayu dengan Metode PROMETHEE untuk Pemilihan Supplier Terbaik di CV AIDA - Arifin, Qanita Zahira Muhar; Rochmoeljati, Rochmoeljati (BRILIANT: Jurnal Riset dan Konseptual, 2026)
CV Aida is a company engaged in furniture manufacturing. The purpose of this research is to select the best supplier for CV Aida. This study uses primary data in the form of CV Aida's supplier criteria obtained through interviews and questionnaires with three employees who understand the company's suppliers, as well as secondary data in the form of a list of teak wood suppliers and literature studies as the basis for determining the criteria. The dependent variable is the best alternative supplier of wood raw materials for CV Aida, while the independent variables are the supplier selection criteria derived from the literature and interview results. Data processing is carried out using the AHP method to determine the weights of criteria and subcriteria, and the PROMETHEE method to evaluate and determine the best supplier based on these criteria.. The finding indicates that the top-ranked supplier is UD Tulus with a net flow of 0.427. UD Barokah is ranked second with a net flow of 0.09225. Meanwhile, UD Ikhwan Kayu occupies the third rank with a net flow of -0.132. Although UD Ikhwan Kayu has a negative net flow, it is still better than UD Hikmah and UD Agung Kayu, with net flows of -0.15475 and -0.2325, respectively.